Effects of Admixtures on Slag-fly ash Geopolymer Cementing Slurry - Wang, Siyi; Yang, Hao; Yang, Shihan; Chen, Jiebin; Wang, Zhuoyinan; Sun, Guiyi (Tezhong Youqicang = Special Oil & Gas Reservoirs, 2022)
To address the problems of short setting time, high apparent viscosity and great filter loss of geopolymer cementing slurry, the effects of retarder, dispersant and fluid loss agent on geopolymer cementing slurry were studied based on the performance parameters such as setting time, apparent viscosity and filter loss. The results showed that, the retarders barium chloride and borax only had weak retarding effect, while sodium fluorosilicate had a good retarding effect and could improve the compressive strength of set cement; the dispersant sodium lignosulfonate and the naphthalene water reducer had a certain dispersibility, and the naphthalene water reducer had a better viscosity reduction effect than sodium lignosulfonate at the same injection rate, while the polycarboxylate water reducer showed a thickening effect; the fluid loss agents CMC and CMS were significantly effective in fluid loss reduction, CMS was superior to CMC in terms of fluid loss reduction at the same injection rate, and both of them could